Workshop Eco Enzyme: Pengembangan Kompetensi Pendidik dalam Mengintegrasikan Inovasi Ramah Lingkungan untuk Pembelajaran Berkelanjutan di Desa Kagungan Ratu Pesawaran - Irawansyah; Farhan Barata, Muhammad (SAKALIMA: Pilar Pemberdayaan Masyarakat Pendidikan, 2024)
Global environmental issues, such as climate change and pollution, demand an education system that equips younger generations with environmental awareness and sustainable skills. This study aims to enhance educators' competence in integrating environmentally friendly innovations through an Eco Enzyme Workshop held in Kagungan Ratu Village, Pesawaran. The workshop involved 10 educators as research subjects, selected based on their engagement in environmental teaching programs. The study employed a descriptive qualitative approach using observation, questionnaires, and interviews to evaluate the workshop's effectiveness. The results showed an improvement in participants' understanding of the benefits of eco enzyme in promoting environmental cleanliness and its potential application in education. A total of 60% of participants demonstrated a strong understanding, while 30% had a moderate comprehension, and 10% required further clarification. These findings affirm that eco enzyme can serve as an effective solution in supporting environmentally focused educational practices while reducing reliance on harmful chemicals. For future research, a more in-depth study is recommended to examine the impact of eco enzyme implementation on student behavior in schools, as well as a long-term evaluation of its effects within the educational context.